Technical and Financial Feasibility Study of A 10 MW Waste-Power Plant Construction Project - Swempri Agung Prasetyo (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study evaluates the technical and financial feasibility of developing a 10 MW Waste-to-Energy Power Plant (PLTSa) in Tembilahan City as an integrated response to urban waste management problems and increasing electricity demand. Research Method: A quantitative techno-economic feasibility approach was employed. Waste generation was measured in accordance with SNI 19-3964-1994, yielding 0.376 kg/person/day. Energy potential was analyzed using an assumed Lower Heating Value of 3,674 kcal/kg under three technology scenarios: pyrolysis, incineration with combined heat and power, and gasification. Financial feasibility was assessed using Net Present Value, Benefit-Cost Ratio, Internal Rate of Return, and Payback Period at a 10% discount rate. Results and Discussion: Gasification demonstrated the highest feasibility, with an NPV of IDR 83.03 billion, a B/C ratio of 1.86, an IRR of 15%, and a payback period of 12.8 years. Pyrolysis and incineration were less feasible due to lower conversion efficiency. However, project viability remains sensitive to assumptions about waste calorific value and cost. Implications: WTE planning should consider local waste characteristics, technology-specific costs, and operational risks to support realistic policy decisions. Originality: This study provides a context-specific techno-economic assessment of PLTSa development in a non-metropolitan city in Indonesia.